The Impact of Using 3D Simulator on Learning Motivation of Nursing Students - Azjunia, Atiq Rizka; Komariah, Maria; Setiawan, Setiawan (Universitas Padjadjaran, 2024)
In the development of the world of technology and information, technological innovations continue to be promoted by humans to this day, one of the innovation is 3D technology. This interactive 3D simulator learning media, it is felt that it will further motivate students in learning, without motivation it is very possible if students are lacking in learning. To find out whether the use of 3D simulators has an impact on learning motivation of Padjadjaran University Nursing students. This research applied quantitative research, with preexperimental and using One-Group Pretest-Posttest. The sample in this study amounted to 54 respondents, with the sampling technique purposive sampling. The instrument used is the Academic Motivation Scale (AMS). Then, analyzed univariate and bivariate using SPSS application version 25 for windows. Results: The p value indicated a significant difference between the pretest and posttest groups with p=0.03 (p<0.05). The use of 3D simulators as learning media can increase nursing students’ learning motivation. So, we suggest that this research can be considered by tertiary institutions as a medium to support teaching and learning processes.